Some new characteristics of the confined flow over circular cylinders at low reynolds numbers - Ooi A.; Chan L.; Aljubaili D.; Mamon C.; Leontini J.S.; Skvortsov A.; Mathupriya P.; Hasini H. (Elsevier B.V., 2023)
Channel flow; Reynolds number; Cylinder flows; Floquet stability analysis; Low Reynolds number; Three-dimensional flow; Transition Reynolds number; Two-dimensional instability; Two-dimensional simulations; Unsteady three-dimensional flows; Circular cylinders